Sound radiation characteristics analysis for the honeycomb reinforced laminated structures with viscoelastic material fillers through the asymptotic homogenous method. (1st August 2020) - Zhou, X.Q.; Zhang, S.Q.; Lin, W.W.
Abstract: In this study, the sound radiation characteristics of the laminated structures reinforced by honeycomb and composed by viscoelastic material was investigated. Temperature- and frequency-dependent behaviors of the viscoelastic material were considered in this analysis, those parameters affected the dynamics effective properties of the composite structure. After the dynamic equivalent effective stiffness and the dynamic deformation of the structure are determined according to the homogenous asymptotic method, the sound radiation behaviors of the structures in fields of frequency and temperature are achieved. Consequently, the sound radiation characteristic, such as the sound pressure in far-field and the sound radiation efficiency that influenced by the geometry dimensions of the honeycomb structure was examined. Finally, the study is validated by the degeneration method with a degeneration mathematical model that performed in the published literature.